Pemikiran Tok Pulau Manis dan pengkategorian kata-kata hikmah dalam Kitab Syarah Hikam - Mohd Azrai, Mohd Salleh (2025)
Sufism is the spiritual essence within Islamic teachings that plays an important role in the purification of the soul and the formation of noble character. The purpose is to draw closer to Allah SWT and to distance oneself from worldly influences that lead to distraction. However, the appreciation of spirituality and Sufism is increasingly marginalised in the current formal education system, thus contributing to various social issues within modern society. One of the methods to address this issue is by delving into the thoughts of Tok Pulau Manis in the Kitab Syarah Hikam. However, this book is difficult for the public to understand due to its use of archaic language. Therefore, this study is conducted to highlight the wise words of Ibn Atha’illah al-Sakandari as explained by Tok Pulau Manis in the Kitab Syarah Hikam, using language and explanations that are easier to comprehend. There are three objectives in this study: first, to examine the factors influencing Tok Pulau Manis' thoughts; second, to analyse the form of Tok Pulau Manis' thinking; and third, to study the classification of aphorisms in Tok Pulau Manis' Kitab Syarah Hikam. This qualitative study employs library research and in-depth interviews as methods for data collection, while content analysis is used to analyse the collected data. The findings of the study reveal that Tok Pulau Manis's family background, education and his position as a religious advisor have significantly influenced the development of his thoughts, establishing him as a prominent scholar. His ideas on matters of creed (aqidah), Islamic law (sharia), and ethics (akhlaq) are not only relevant but also capable of providing valuable guidance for modern society. The implications of this study are clearly significant, as it paves the way for the application of Sufi values in daily life, thereby addressing the social challenges faced by contemporary society. Additionally, this study has the potential to strengthen spiritual education at all levels of society to achieve well-being and inner peace.